PENGARUH CITRA MEREK DAN KUALITAS PRODUK PAKAIAN BEKAS BRANDED TERHADAP MINAT BELI KONSUMEN KALANGAN MAHASISWA UNIVERSITAS BUANA PERJUANGAN DAN UNIVERSITAS SINGAPERBANGSA KARAWANG - Zahra, Refah Raslina; Fadilla, Arif (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine, analyze, and at the same time explain the description of each variable, the magnitude of the relationship between brand image and product quality in the use of branded used clothing, as well as the partial and simultaneous influence of brand image and product quality on purchase intention on consumer use. branded used clothing, using quantitative methods and using descriptive analysis and verification. The inspection tool used is regression analiysis. The sample used in this study was 379 respondents from a population of 30,126.. Field information sorting procedures are complemented by online opinion polls The results showed that brand image and product quality had a fairly strong relationship, namely 0.597. Brand image has a partial impact of 0.231 or 23.1% on purchase intention. Product quality has a partial impact of 0.304 or 30.4% on purchase intention. The simultaneous effect of brand image and product quality on purchase intention is 0.533 or 53.5% so that brand image and product quality have a positive and significant value on buying interest in branded used clothing, while the remaining is 0.465 or 46.5%. influenced by various factors that were not analyzed.